Anestezjologia i intensywna terapia A retrospective analysis of high thoracic epidural anesthesia and analgesia in cardiac surgery over the 1995-2002 period - Stříteský, Martin; Lipš, Michael; Rubeš, David; Cermak, Tomas; Pavlíková, Marketa; Lindner, Jaroslav (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2005)
Background: According to many studies, high thoracic epidural anaesthesia (TEA) offers various advantages over general anaesthesia for patients undergoing cardiac surgery. On the other hand, there is a potential risk for development of epidural haematoma with serious neurological consequences. Studies concerning this problem are inhomogeneous and refer to about 6,000 patients in total. Because of more than ten years of experience with TEA, we decided to determine the risk of serious neurological complications associated with TEA. This is the largest single-center series of patients who underwent a cardiac surgical procedure under TEA and general anaesthesia. Material and methods: A single-center retrospective analysis of the perioperative course of all patients undergoing cardiac surgery from 1995 to 2002 was performed. The primary endpoint was incidence of spinal cord compression such as radicular back pain or progressive neurological deficits in patients who had cardiac surgery under combined general and TEA. A secondary endpoint was a comparison of outcome between the groups of patients with TEA and balanced anaesthesia. Results: Records of 3,966 patients were analyzed. A group of 1,519 patients underwent cardiac surgery with TEA and 2,447 patients in balanced general anaesthesia. In the TEA group, no patient showed a sign of spinal cord compression until hospital discharge. Patients in the TEA group were extubated earlier (11 hours of mechanical ventilation vs. 13 hours in the GA group, P<0.00001), but there was no difference in the other analyzed variables (mortality, ICU stay, incidence of stroke, atrial fibrillation, postoperative myocardial infarction, pulmonary and wound infection). Conclusion: General anaesthesia combined with TEA is relatively safe and allows earlier extubation than general anaesthesia in cardiac surgery.